The Implementation of the Soka Sari Dance Tradition in the Community of Sari Village, Sape District, Bima Regency - Fadillah, Rozi; Haslan, Muhammad Mabrur; Alqadri, Bagdawansyah; Zubair, Muh. (Universitas Islam Negeri Sumatera Utara, 2025)
The Soka Sari dance tradition is a cultural heritage preserved by the people of Sari Village, Sape District, Bima Regency. This research aims to describe the implementation of the Soka Sari Dance tradition in Sari Village. The method used is qualitative with an ethnographic approach. Data collection techniques include interviews, observation and documentation, while data analysis is carried out through reduction, presentation and drawing conclusions. The research results show that the Soka Sari Dance is carried out in three stages, namely: (1) preparation stage with the provision of traditional materials; (2) the implementation stage which includes the ritual of opening the douma mpaa safety bill (player safety), kalondo buja tumba lamonca (lowering the spear), handing over the buja lamonca (spear) from the guard to the player, wura bongi monca (sprinkling of yellow rice), and the Soka Sari Dance game; and (3) the closing stage in the form of respect. This tradition contains religious, cultural and social values that are still preserved and inherited by society.